Evaluation of Chatbot AI Application in Accounting Learning in High Schools: Challenges and Impacts - Ratri Ratna Sari; Suyatmini Suyatmini (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to explore the implementation of AI chatbot as a learning aid in accounting subjects at SMK Batik 1 Surakarta. With a background to the need for learning innovations that can meet the expectations of the digital generation and improve learning effectiveness, the study examines the potential and challenges of the application of AI chatbots. Through a qualitative descriptive approach, the research gathers data from students, teachers, and school managers to understand the perceptions, efficiency, and obstacles in the use of AI Chatbots in accounting learning. Research results show that the use of AI chatbots can enhance learning interaction, provide real-time feedback, and tailor learning materials to suit the individual needs of students. However, challenges such as the constraints of AI's understanding of specific contexts, the need for personal interaction, as well as issues of data security and privacy are concerns to be addressed. The research also found that the training and adaptation of teachers is an important aspect of the integration of this technology into the learning process.